Thermodynamic Response Enhanced by Sloshing in Marine LNG Fuel Tanks: Experimental Work and Numerical Modelling - Grotle, Erlend Liavåg (NTNU, 2018)
This thesis presents studies of sloshing and how it influences thermodynamic conditions in liquefied natural gas (LNG) fuel tanks. Liquid in a moving tank mixes more efficiently with the gas, which condenses and is followed by a drop in pressure. This issue is relevant for the operation of LNG-fuelled vessels, where the system pressure may drop rapidly under severe motion. To compensate for the pressure loss, it may become necessary to derate the engines, or, in the worst case, perform a complete shutdown of the gas-fuel system. The long-term objective of the research is to improve the operational reliability of LNG-fuelled vessels by performing design improvements or operational measures. LNG has become increasingly popular as a marine fuel due to its low emissions compared to those from conventional fuels like heavy fuel oil (HFO) and marine diesel oil (MDO). Low-pressure LNG fuel systems are designed similarly to landbased storage facilities. The storage tanks are vacuum-insulated and pressurized such that heat ingress is minimal. But when the tank is pressurised, the liquid may be significantly colder relative to the saturated condition. The thermal equilibrium is controlled in the short term by the liquid due to its large mass. The sloshing enhances the internal energy transfer, and the final state corresponds to a state that is closer to the initial liquid temperature. This research is based on experimental work, analysis, modelling, and simulations. An experimental facility was designed and constructed, experimental tests were conducted separately, with a transparent tank for hydrodynamic studies and a pressurised steel tank for analysis of the thermodynamic response. Hydrodynamic sloshing tests were conducted with both rectangular and cylindrical tanks. Computational fluid dynamics (CFD) simulations of sloshing hydrodynamics were carried out with both tank geometries with the aim of replacing the hydrodynamic experiments to investigate any tank shape, inner structure, or motion. The resulting sloshing ...